Art and Sovereignty in Global Politics
XIV, 320 p. 15 illus., 9 illus. in color.
Keywords: This volume aims to question, supplement, and revise current understandings of the relationship between aesthetic and political operations. The authors transcend disciplinary boundaries and nurture a wide-ranging sensibility about art and sovereignty, two highly complex and interwoven dimensions of human experience that have rarely been explored by scholars in one conceptual space. Chapters consider the intertwining of political structures and modernist artistic forms, including the relationships between nationalism and official portraiture, museums and cultural property, and territoriality and architectural history. Other chapters examine populist politics that emerged as art became commercialized and mediated, engaging industrial design and popular entertainment industries, and producing national and minority cinema, ethnic crafts for domestic markets, and performance art that contests national citizenship. In exploring the nexus of art and sovereignty, contributors highlight power relations and provide critical commentary on repercussions of colonialism and notions of universal truths rooted in Western ideals. By interfering with established dichotomies related to art and sovereignty, all contributors fuel a resistance to traditional definitions of “Art” and encourage a new perspective on the co-constitution of artworks and practices of sovereignty. .